Electrochemical Characterization of Electrodeposited Ni-titanium Dioxide Deposits on Copper and their Corrosion Study - BERARMA, Khadidja; RAGHDI, Amina; BENAICHE, Ghania (Nepal Journal of Science and Technology, 2021)
This work aimed to produce and characterize composite coatings of nickel incorporating TiO2 nanoparticles on a copper substrate. These deposits were obtained from watts bath. In the study, the cyclic voltammetry technique was employed to provide a better understanding of the cathodic behavior of nickel deposition. The effects of the potential scanning rate and the effect of cathodic limits on cyclic voltammograms deposition of Ni in Primitive Watts Bath (BWP) were determined. The composite coatings of nickel incorporating TiO2 nanoparticles were characterized using various electrochemical techniques such as open circuit potential (OCP) and potentiodynamic polarization measurements, and electrochemical impedance spectroscopic methods. The current density values for the Ni-TiO2 in the case of 5 g/L and 10 g/L of TiO2 determined from the polarization curves recorded in 3.5% NaCl indicate that the corrosion process on nickel incorporating the TiO2 nanoparticle composite surface is slower than on pure nickel. The TiO2 particles embedded in the electroplated nickel, increase the polarization resistance and decrease the corrosion rates as compared with electrodeposited pure nickel. Electrochemical impedance spectra obtained at the open-circuit potential ( OCP) in 3.5% NaCl showed an increase of polarization resistance with time in all cases.